2019
DOI: 10.3390/su11113086
|View full text |Cite
|
Sign up to set email alerts
|

Environmentalism and Polish Coal Mining: A Multilevel Study

Abstract: This paper, drawing on a questionnaire survey conducted among 587 coal miners from six coal mines, seeks to ascertain whether the Polish coal mining industry is committed to organizational greening and whether its employees behave in environmentally responsible ways. Specifically, it explores—by means of hierarchical linear modeling (HLM)—the direct effects of green organizational climates on miners’ pro-environmental conduct at home and at work. We found that climates had a direct effect on employee behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Prior literature notes the importance of studying the effect of individual environmental concerns on PEB (Bak, 2018). However, the studies on personal environmental awareness and environmental concern as antecedents of employees' voluntary PEB at work are scarce (Zientara et al. , 2019) and inconsistent, presenting contradictive results: ones state that the previously mentioned variables promote such behavior while the others claim that the relationship is not statistically significant (Yang et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior literature notes the importance of studying the effect of individual environmental concerns on PEB (Bak, 2018). However, the studies on personal environmental awareness and environmental concern as antecedents of employees' voluntary PEB at work are scarce (Zientara et al. , 2019) and inconsistent, presenting contradictive results: ones state that the previously mentioned variables promote such behavior while the others claim that the relationship is not statistically significant (Yang et al.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decades the awareness and transposing values of society towards environmental issues are growing (Karman and Savanevi cien_ e, 2020). Corporate social responsibility (CSR) and sustainable approaches are particularly relevant for emerging countries, since it allows free and active integration of these countries into the global economic and political system (Zientara et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Zientara et al [ 37 ] linked employee education to individual factors, such as beliefs or awareness. They indicated that people who are aware of environmental threats may be more eager to segregate and recycle waste, purchase ecological products, or commute to work by public transport.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Although the importance of the mining industry has slightly decreased in EU countries, it still constitutes a crucial sector of the economy. Both mineral and energy raw materials extracted in EU countries make it possible to significantly satisfy their energy needs (e.g., Poland, Germany) [21][22][23][24][25][26][27] and provide raw materials used in almost all economic sectors (construction, chemical, pharmaceutical, space, automotive, electronic, and other industries) [28]. Contemporary economies of both developing and developed countries cannot function without gas, oil, iron ore, or copper.…”
Section: Introductionmentioning
confidence: 99%